Phacoemulsification Combined with Goniosynechialysis and Goniotomy fzor Primary Angle-Closure Glaucoma: A Mini Systematic Review - Ryan Cahya Firdaus; Andaru Cahya Sekarini; Agus Ariyanto; Ihsan Hanif (GLOBAL HEALTH SCIENCE GROUP, 2026)
Primary angle-closure glaucoma (PACG) is a major cause of irreversible blindness and is commonly associated with elevated intraocular pressure (IOP). Objective to evaluate the effectiveness and safety of combining phacoemulsification (PEI), goniosynechialysis (GSL) or visco-goniosynechialysis (VGSL), and goniotomy (GT) in the management of PACG. A mini systematic review was conducted using Google Scholar, PubMed, and ProQuest up to March 2025. Eligible studies evaluating combined PEI, GSL/VGSL, and GT in PACG patients were screened independently by two reviewers and analyzed descriptively. Five studies involving 534 eyes from 475 patients were included, comprising two retrospective case series, one randomized clinical trial, and two multicentre observational studies. Follow-up periods ranged from one week to 24 months. Across studies, the combined procedure consistently demonstrated significant reductions in IOP and glaucoma medication use, while reported complications were generally mild and self-limiting. Combined PEI, GSL/VGSL, and GT appears to be a safe and effective surgical option for PACG with coexisting cataract. This review contributes to the growing evidence supporting angle-based surgical interventions for improving IOP control and reducing medication burden in PACG.